Histone proteolysis: A proposal for categorization into 'clipping' and 'degradation'. (28th October 2014) - Dhaenens, Maarten; Glibert, Pieter; Meert, Paulien; Vossaert, Liesbeth; Deforce, Dieter
<x xml:space="preserve">Abstract</x> We propose for the first time to divide histone proteolysis into "histone degradation" and the epigenetically connoted "histone clipping". Our initial observation is that these two different classes are very hard to distinguish both experimentally and biologically, because they can both be mediated by the same enzymes. Since the first report decades ago, proteolysis has been found in a broad spectrum of eukaryotic organisms. However, the authors often not clearly distinguish or determine whether degradation or clipping was studied. Given the importance of histone modifications in epigenetic regulation we further elaborate on the different ways in which histone proteolysis could play a role in epigenetics. Finally, unanticipated histone proteolysis has probably left a mark on many studies of histones in the past. In conclusion, we emphasize the significance of reviving the study of histone proteolysis both from a biological and an experimental perspective. Also watch the Video Abstract.